The Debate Over the Definition of Basic Income - Karl Widerquist (19757040) (2024)
The basic income movement is in the midst of a substantial internal debate about the definition of basic income. The current debate focuses mostly on two questions: (1) Should the definition be restricted to a payment that is uniform with respect to income (a non-means-tested grant delivered to high- and low-income people alike)? (2) Should the definition include a threshold such as one stipulating that the grant is large enough to live on? Although this article recommends keeping the current definition in place, its central point is not whether one definition is best but that the definitional issue is far more complex than simple question of how to define one term. This complex issue cannot be resolved by any organization clarifying its definition of basic income. These two questions identify a family of up to nine closely-related concepts have been and will continue to be used in the discussion of policy options along the lines of an unconditional cash payment. The discussion needs language that will allow people on all sides of the controversies behind these two questions to clearly discuss all options. That means we need not one but several terms. Therefore, the main goal of this paper is to identify the various concepts that need to be clearly identified. We need to start thinking about nonpejorative terms for the members of this family of concepts so that people on all sides of the relevant issues can share the terminology they need to have fruitful discussion. A true resolution is better found through dialogue with people on all sides of the issues rather than by the unilateral declaration of people on one side or the other. Other Information Published in: Basic Income Studies License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1515/bis-2024-0021